Relationship Between Elderly Body Composition Indices and Static and Dynamic Balance in Relation to Their Rate of Falling - Elham Azimzadeh; Meysam Gholamali; Maryam Nourshahi (University of Social Welfare & Rehabilitation Sciences, 2013)
Objectives: The purpose of this study was to investigate relationship between body composition indices with static and dynamic balance and rate of falling in active elderly people. Methods & Materials: This research was a correlation study. Active elderly women volunteered for participation in this research (n=45). Body composition indices (body fat mass, fat free mass, body mass index, waist to hip ratio) measured with the body composition analyzer. Static and dynamic balance measured by Biodex, with postural stability and fall risk tests, respectively. Also, the rate of falling in the previous 1- year asked for subjects. Statically analyses performed with the Pearson correlation test, significant level was set at P≤0.05. SPSS software was used. Results: The results of this study showed all of body composition indices have significant correlation with static and dynamic balance and rate of falling (P≤0.05). Conclusion: The finding of this research showed that all of body composition indices have significant correlation with static and dynamic balance and rate of falling in active elderly people. Therefore, it seems physical activity through improvement of body composition indices in active elderly people, causes improvement of static and dynamic balance and lowering the rate of falling.